Characteristics of the flight arc in horses jumping three different types of fences in Olympic competition - Clayton, H. M.; St. George, L.; Sinclair, J.; Hobbs, S. J. (Journal of Equine Veterinary Science, 2021)
Show jumping horses must execute fences of varying height and width, but the effect of this on jumping kinematics during the airborne phase have not been described. The aim of this study was to describe differences within- and between-horses in CM trajectory, trunk orientation and average trunk angular velocity in a group of elite horses executing three fences: vertical fence (1.60 m), spread fence (1.50 × 1.80 m), water jump (4.5 m) during an Olympic competition. Two-dimensional kinematic data (60 Hz) were collected from video cameras set perpendicular to each fence. After manual digitization, linear and angular variables related to the position and rotation of the CM and trunk were calculated. Linear fixed effects models evaluated within-group differences between fences and kinematic variables. Repeated measures correlation (rmcorr) evaluated within-horse associations between kinematic variables and fence type. Compared with the water jump, CM vertical velocity, CM peak height, and average trunk angular velocity were significantly higher (P < .05) and CM horizontal velocity was significantly lower (P < .05) for the vertical and spread fences. Peak CM height coincided approximately with the middle of the spread fence, toward the take-off for the water jump and landing for the vertical fence. The trunk was significantly more inclined at take-off for the vertical fence and significantly less inclined for the water jump at landing. Rmcorr analysis revealed that individual horses generally employ similar jumping techniques for each fence type. Findings provide original insight into the mechanical requirements for elite horses jumping different fence types.